2018
DOI: 10.1002/med.21492
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active quinoline and quinazoline alkaloids part II

Abstract: To follow-up on our prior Part I review, this Part II review summarizes and provides updated literature on novel quinoline and quinazoline alkaloids isolated during the period of 2009-2016, together with the biological activity and the mechanisms of action of these classes of natural products. Over 200 molecules with a broad range of biological activities, including antitumor, antiparasitic and insecticidal, antibacterial and antifungal, cardioprotective, antiviral, anti-inflammatory, hepatoprotective, antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(98 citation statements)
references
References 222 publications
(507 reference statements)
2
96
0
Order By: Relevance
“…Differential comparison also revealed that kanamycin resistant Y. pestis produces significantly lower amounts of 3-(2-chloro-5-hydroxyphenyl)-2-methylquinazolin-4-one and isopropylhydroxylamine, relative to the wildtype strain (~ 800 and 8,000 fold lower, respectively). The quinazolinone alkaloids are a large family of secondary metabolites produced by plants, fungi, and bacteria 28 30 . Alterations to primary metabolism is well known to alter production of secondary metabolites 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Differential comparison also revealed that kanamycin resistant Y. pestis produces significantly lower amounts of 3-(2-chloro-5-hydroxyphenyl)-2-methylquinazolin-4-one and isopropylhydroxylamine, relative to the wildtype strain (~ 800 and 8,000 fold lower, respectively). The quinazolinone alkaloids are a large family of secondary metabolites produced by plants, fungi, and bacteria 28 30 . Alterations to primary metabolism is well known to alter production of secondary metabolites 31 .…”
Section: Resultsmentioning
confidence: 99%
“…4-Hydroxy-2(1H)-quinolone is a unique structural motif mostly found in alkaloids from rutaceous plants (family Rutaceae) [1,2]. This motif has several tautomeric forms including 2,4-dihydroxyquinoline [3], although which tautomer to be taken seems not always be identified in some of the studies.…”
Section: Introductionmentioning
confidence: 99%
“…Quinolines are one of the most ubiquitous structural units in natural products, [1][2][3][4][5] biologically active compounds [6][7][8][9][10][11] and functionalized materials ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%